Celebration of ESREA’s thirty years. An (auto)ethnographical account on adult education as a field of study - Bron, Agnieszka (Adult Education Discourses, 2023)
This article is the story of a leading European association of researchers on the education of adults and adult learning. The European Society for Research on the Education of Adults (ESREA) is celebrating its thirtieth anniversary in 2022. By looking back and recalling how the association started, who its initiators were, and using an (auto)ethnographic and biographical method of data collection and narration, the aim is to introduce a debate on adult education as evolving towards social sciences. At the same time asking a question how crucial was ESREA’s impact on adult education research, if at all. In the concluding part, a state of adult education as a social science discipline is presented and discussed.